English as a Medium of Instruction in Public Schools: Dreams and Realities - Silwal, Gokul; Paneru, Sunita (Jana Adarsha Research Journal, 2026)
This research articles aims to explore the factors which attracted public schools based in rural setting adopting English as a medium of instruction and to reveal the difficulties in practicing EMI in classroom. This qualitative research design has employed narrative inquiry as a method of study. The researcher selected the participants purposively. They were stakeholders from school administration, management committee, parents, teachers, and students. The narratives and experiences of the participants were collected through semi-structured interviews, using a questionnaire, informal conversation, taking notes and online communication. The responses were recorded, transcribed, and thematically analyzed. The data analysis showed that the adoption of EMI was the result of parents’ pressure, dreams to bring quality in education, to retain students in public school. However, it was not easy to practice EMI in the classroom effectively. The teachers lack pedagogical skills and proficiency, the school environment is not EMI friendly, and students come from diverse linguistic and cultural backgrounds. Therefore, it takes time to convert dreams of EML into reality in public schools.